Transfer, Amplification, Storage, and Complete Self‐Recovery of Supramolecular Chirality in an Achiral Polymer System. (16th July 2021) - Miao, Tengfei; Cheng, Xiaoxiao; Ma, Haotian; He, Zixiang; Zhang, Zhengbiao; Zhou, Nianchen; Zhang, Wei; Zhu, Xiulin
Abstract: Supramolecular chirality and its complete self‐recovery ability are highly mystical in nature and biological systems, which remains a major challenge today. Herein, we demonstrate that partially cross‐linked azobenzene (Azo) units can be employed as the potential chiral trigger to fully heal the destroyed helical superstructure in achiral nematic polymer system. Combining the self‐assembly of Azo units and terminal hydroxyl groups in polymer side chains allows the vapor‐induced chiral nematic phase and covalent fixation of the superstructure via acetal reaction. The induced helical structure of Azo units can be stored by inter‐chain cross‐linking, even after removal of the chiral source. Most interestingly, the stored chiral information can trigger perfect chiral self‐recovery (CSR) behavior after being destroyed by UV light, heat, and solvents. The results pave a new way for producing novel chiroptical materials with reversible chirality from achiral sources. Abstract : The storage and complete self‐recovery of supramolecular chirality in an absolute achiral azobenzene‐containing polymer system is successfully achieved for the first time.